تحديث اللغة العربية بين المحافظة والتماهي (El-Wahat Journal for Research and Studies, 2017)
The Arabic Language Has Undergone Great Developments Until It Has Settled Itself In The Manner In Which The Holy Quran Came Down. The Arabic Language Has Not Stopped At That Point. Like Many Other Living Languages, Both The Process Of Evolution And Internal As Well As External Influences Have Forced The Arabic Language To Continue The Process Of Linguistic Evolution, Preserving Its Original Characteristics That Distinguish It From Others. The Arabic Language Is In Constant Change Thanks To  The Enormous Capacity Of Its Morphological System That Can Cope With Any Linguistic Changes Required For Any Era.      As The Fascination With The Western Modern Civilization And Blind Imitation Spread, There Were Calls For Linguistic Conformity With The Other, No Matter How Different Or Contradictory This Is To Our Original Linguistic Identity, Claiming That This Was The Desired Modernization.       Indeed, These Claims  Only Based On A Narrow Or Blind Vision Of The Concept Of Modernization, That Rely On Misleading Interpretation Of Data Beyond Its Intended Meaning; Classical Arabic Cannot Be A Reflection Of The Image Of Other Languages As It Is Quite Unique In Its Structure And Use.       Keywords    -       Modernization - Preservation - Identification - Renewal - Originality - Linguistic Assimilation